The values of electricity saving for consumers. (December 2018) - Innocent, Morgane; Francois-Lecompte, Agnès
Abstract: This study aims at understanding the perceived value to consumers of practicing electricity saving. Based on an exploratory qualitative investigation and on two quantitative surveys, our study seeks to identify the values of electricity saving and model their relation with the intensity of electricity-saving behaviours. The results point to seven components of positive or negative assessments linked to the practice of electricity saving. These can be described in terms of environmental and citizen aspects, household management, feelings of well-being, secondary benefits, daily efforts, social consequences and lack of knowledge. Our results suggest that the main value lever of electricity-saving for consumers is more closely linked to well-being rather than environmental or money-saving concerns. These findings lead us to formulate new recommendations for public authorities to support their efforts in reducing residential electricity consumption. Highlights: We explore how electricity savings are experienced by consumers. The positive and negatives values of electricity savings cover a wide range. Behaviour is better predicted by individualistic rather than environmental considerations. We suggest a virtuous cycle of practices related to electricity savings. Public programmes should focus on consumers' daily routines rather than on their knowledge.